Analisis pengaruh pengangguran, penanaman modal dalam negeri, dan upah minimum provinsi terhadap kemiskinan di Jawa Timur - Luqiana Putri, Thalita; Eviana Hutabarat, Ruth (Jurnal Riset Pendidikan Ekonomi, 2024)
Poverty is a serious problem that needs to be addressed because it can make it difficult for people to meet basic needs and an average standard of living. This research aims to determine the effect of unemployment, PMDN, and UMP on poverty in East Java. The data used in this research is secondary data obtained from BPS and NSWi from 2001 to 2022 in the East Java region. The analysis technique used in this research is multiple linear regression analysis using the data processing tool EViews 12. The results of this research show that unemployment has a positive and significant influence on poverty in East Java. Meanwhile, PMDN and UMP have a negative and significant influence on poverty in East Java. Unemployment, PMDN, and UMP together have a significant influence on poverty in East Java. Poverty reduction can be achieved through training and education programs that are in line with job market demands, as well as by determining an adequate UMP in line with Decent Living Needs.